Gonadal aspects, testosterone and estradiol profiles of the Lebranche mullet Mugil liza subjected to different temperatures during the larviculture phase - Marco Shizuo Owatari; Vanessa Martins da Rocha; Cleize Sales da Silva; Marina Cesconeto dos Santos; Mariana Rangel Pilotto; Fabiola Santiago Pedrotti; Caio Magnotti; Maurício Laterça Martins; Vinicius Ronzani Cerqueira (Ciência Animal Brasileira)
In Brazil, the Lebranche mullet is the most important Mugilidae species for the fishing industry. However, recently, the species has been recommended for classification as near threatened. In this sense, aquaculture has emerged as a powerful tool for natural resource conservation and development. The present study evaluated the influence of different temperatures during Mugil liza larviculture and their late effects on gonadal development and hormonal quantification after 24 months. The fertilized eggs (45 eggs L-1) were initially kept in a 60 L circular tank until hatching. After hatching, the larvae were subjected to four treatments in triplicate at different temperatures (21, 24, 27 and 30 °C) for 35 days. The juveniles were subsequently transferred to growth units where they remained identified, according to the treatments, for 24 months. The weight and length of the fish were significantly different in the larviculture phase. Histological analyses revealed immature, maturing, and mature male gonads. The estradiol levels in the fish were low, regardless of the maturation stage. For testosterone, the highest values were observed in mature males (1.29 ± 0.07 ng mL-1). No significant differences were observed (p > 0.05) in the concentrations of estradiol and testosterone in relation to temperature. However, there were significant differences (p < 0.05) in testosterone concentration depending on sexual maturation. The results suggest that temperature exerts a masculinizing effect on M. liza. Furthermore, temperature directly affected larval growth. In summary, the results provide evidence that temperature may play a crucial role in sex determination in M. liza.